2006
DOI: 10.1536/ihj.47.173
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Angiotensin-Converting Enzyme Inhibitors or an Angiotensin Receptor Blocker in Combination With Aspirin and Cilostazol on In-stent Restenosis

Abstract: SUMMARYIt remains to be determined whether adding an angiotensin-converting enzyme inhibitor (ACEI) or an angiotensin II receptor blocker (ARB) to antiplatelet therapy has a therapeutic benefit on in-stent restenosis.After successful coronary stenting, 165 patients (167 lesions) were randomly assigned to a basal (aspirin 162 mg + cilostazol 200 mg/day), ACEI (basal treatment + quinapril 10 mg or perindopril 4 mg/day), or ARB (basal treatment + losartan 50 mg/day) treatment group. Quantitative coronary angiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Sixteen of these studies were excluded for the following reasons: three of them were not clinical trials; [1,2,4] three of them compared different types or dosages of ARBs rather than comparing the risks with and without an ARB; [5][6][7] four studies provided none of the outcomes of interest; [8][9][10][11] two studies reported only stent number and not patient number; [12,13] the other four studies were excluded because they were not randomized controlled trials. [14][15][16][17] Finally, five studies with a total number of 624 patients met the inclusion criteria [18][19][20][21][22] (figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen of these studies were excluded for the following reasons: three of them were not clinical trials; [1,2,4] three of them compared different types or dosages of ARBs rather than comparing the risks with and without an ARB; [5][6][7] four studies provided none of the outcomes of interest; [8][9][10][11] two studies reported only stent number and not patient number; [12,13] the other four studies were excluded because they were not randomized controlled trials. [14][15][16][17] Finally, five studies with a total number of 624 patients met the inclusion criteria [18][19][20][21][22] (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…We Radke et al [19] ( Ujiie et al [20] ( Peters et al [22] ( Effect of ARBs on Neointimal Hyperplasia after Coronary Stent Implantation found it interesting that some studies used an ACE inhibitor as a control [22] while others totally excluded ACE inhibitors in the study. [21] Although ACE inhibitors were able to inhibit neointimal proliferation in animal models, [23,24] they were found to be inefficient in preventing neointimal hyperplasia in humans.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first clinical evi- Clinical research on hypertension has already demonstrated that the efficacy of angiotensin converting enzyme inhibitors or ARBs in ameliorating left ventricular hypertrophy was much greater than that of other kinds of antihypertensive drugs. 17) Experimental research has indicated that autocrine and/or paracrine release of angiotensin II possibly mediates the hypertrophy of cardiac myocytes, 16) while animal studies 14,15) have demonstrated that LVM was reduced by administration of ARB in genetic hypertension or in hypertrophic cardiomyopathy in animal models. These observations strongly support the hypothesis that ARBs inhibit gene expression and reduce LVM of HNCM similarly in humans.…”
Section: Discussionmentioning
confidence: 99%
“…mental and animal studies 14,15) have indicated that angiotensin II 16,17) excretion followed by stretch stimulation or pressure load on the cardiac myocytes was associated with the process of initiation and extension of myocardial hypertrophy. The mechanism of human sarcomere disease, ie, hypertrophic cardiomyopathy, however, is completely veiled in a black-box through which the gene expressions lead to morphological disorders such as interstitial fibrosis with disarray of hypertrophied cardiac myocytes.…”
mentioning
confidence: 99%
“…Stent implantation is used extensively in percutaneous coronary intervention (PCI) and significantly improves the clinical outcome in coronary heart disease, but it is limited by in-stent restenosis which cannot be corrected by drug therapy [1].…”
Section: Introductionmentioning
confidence: 99%